Molecular bases of endometrial cancer: New roles for new actors in the diagnosis and therapy of the disease - Llauradó, Marta (2011)
Endometrial carcinoma (EC) is the most commonly diagnosed gynecologic malignancy in the western world. The majority of these cancers are curable, but a subset about 15–20% of endometrial tumors exhibits an aggressive phenotype. Based on clinic-pathological and molecular characteristics, EC has been classified into two groups: Type I estrogen-dependent adenocarcinomas, which have a good prognosis and an endometrioid histology, and Type II or non-estrogen-dependent EC associated with poor prognosis and non-endometrioid histology. EC develops as a result of a stepwise accumulation of alterations that seem to be specific of each histological type. However, more knowledge is needed to better understand the differences in the biology and the clinical outcome of EC. We would like to highlight the need to explore new potential biomarkers of EC as a tool for the detection and monitoring of aggressive endometrial tumors that, at the same time, will allow us to develop novel and more selective molecular targeted therapies against EC.